(untitled) (lectio difficilior, 2000)
Sexuality is the focus of numerous conflicts in the apocryphal Acts of the Apostles. But what does this really concern? How can sexuality be grasped both as a cultural phenomenon as well as a linguistic problem in these ancient texts? Arguing about sexuality does not necessarily mean rejecting or denigrating it. We must, however, develop an instrument that, with respect to conflict, recognises exactly who is speaking, what the situation is, and what the argument concerns. Thus we need a hermeneutic of conflict, which, analogous to the hermeneutic of suspicion, classifies the wealth of material that exists within the surrounding silence or argument. An examination of the narrative features shows that it is not about rejecting sexuality as such (in favour of religious asceticism, for instance), but about distinguishing when and how sexuality represents an attack on the body or the integrity of another person. Religion contributes in two ways to this 2nd/3rd century discourse on sexuality: first, it makes the discourse possible; and second, it is sensitive to situations of injustice related to sexuality.